Analysis of the Parasitic Motion of 2-PrRS-PR（P）S Parallel Metamorphic Mechanism - Kun Ma; Hongwei Ma; Haibo Tian; Gang Dong (Jixie chuandong, 2019)
Based on the theory of metamorphic，a novel parallel metamorphic mechanism of 2-PrRS-PR（P）S mechanism is proposed which the revolute pair of two limbs can change its rotation axis to achieve the metamorphic configuration. Firstly，the DOF of working configurations are analyzed by using the screw theory. Secondly，according the characteristic of the mechanism，the kinematics model of the parasitic motion is established and the relationship between the parasitic motions and the parameters of the mechanism in different configurations are obtained. Finally, the diagram of the parasitic motion in different configurations is analyzed by simulation software Matlab. The results show that the parasitic motion of the proposed mechanism has different directions in different configurations. The magnitude of the parasitic motion has symmetry with the change of the structure parameters. The analysis of the parasitic motion provides theoretical basis for optimization design and error analysis of the mechanism.